A contextualização no currículo de cursos de licenciatura da área das ciências naturais : uma análise no contexto amazônico - Carvalho, Mary Tânia dos Santos (2019)
This research puts on the agenda curriculum policies for the formation of the Natural Sciences area teachers, the Amazon scenario. Relating the experiences lived between the river and the forest with the motivation to adopt the contextualization in the curriculum of undergraduate courses in the area of Natural Sciences as object of study. Specifically for the following question: How is the Amazon presented in curricular texts of teachers training courses in the area of Natural Sciences of a public university researched? (Research problem): The search for answers to this question led us to the investigation of approach of questions related to the Amazonian life in texts of the curricular policy of the undergraduate courses researched (Biological Sciences, Physics, Chemistry) of the University of the State of Amazonas (UEA), Parintins campus. I share the understanding that life in the Amazon is "a true school of the eye. A Pedagogy of Contemplation. A learning to learn to look "(PAES LOUREIRO, 2006, p 127). So to understand the theoretical support was sought in the cultural field of study's authors, in Curricular Policies for Teacher Training, and Policy Cycle Approach (ACP) Stephen Ball sociologist. The methodological path includes the following procedures: a) Presenting the thesis in liquid language of Amazonas, from authors who favored the establishment of interfaces between culture (conceived in the plural) and knowledge of the Amazonian people; b) Amazon and its liquid Language; c) National curricular policies for Teacher Education in the Natural Sciences area: a look at the principle of contextualization; d) The contextualization in curricula of undergraduate courses in the area of Natural Sciences of the CESP / UEA. We understand that the research on the approach of questions related to the Amazonian life in Pedagogical Projects of Courses (PPC) of Degree in the area of the Natural Sciences potentiates the formation of teachers and the dialogue between academic culture and local knowledge of the Amazon. The obtained data indicate that the documents mix discourses that flow from new theories of the field of science and the field of teacher education (critical theories) with propositions of economicist character based on the development of the competences required by the market, the concept of teacher defended in these documents indicate the articulation between the academic formation and the formation the productive, social and political life, which implies respect to the diversity and the life context of the students.